Responses of microbial necromass carbon and microbial community structure to straw- and straw-derived biochar in brown earth soil of Northeast China - Sun, Qiang; Yang, Xu; Bao, Zhengrong; Gao, Jian; Meng, Jun; Han, Xiaori; Lan, Yu; Liu, Zunqi; Chen, Wenfu (Frontiers in Microbiology, 2022)
Soil microbial organisms are conducive to SOC sequestration. However, little attention has been given to the contributions of living MBC and microbial necromass carbon to the SOC pool under biochar and straw amendments. The aims of the study were to explore 1) the effects of maize straw and biochar on MBC, POC, MAOC, DOC and microbial necromass carbon; 2) the contribution of MBC and microbial necromass carbon to the SOC pool; and 3) the relationships among the soil microbial community structure, microbial necromass carbon and other SOC fractions under maize straw and biochar application for nine consecutive years. Three treatments were studied: CK (applied chemical fertilizer only), BC (biochar applied annually at a rate of 2.625 t ha-1 combined with chemical fertilizer), and SR (straw applied annually at a rate of 7.5 t ha-1). Both biochar and straw increased the SOC contents after nine successive maize plant seasons; the DOC and MAOC contents were also increased by biochar and straw amendments. Biochar had advantages in increasing POC contents compared to straw. Biochar and straw increased MBC contents by 48.54% and 60.83% compared to CK, respectively. Straw significantly increased the Galn, GluN, MurA, ManN and total amino contents (P<0.05); however, biochar significantly increased the Galn and GluN contents (P<0.05) but had no impact on the MurA contents and decreased the ManN contents. Biochar mainly increased the fungal-derived necromass carbon contents but had no effect on the bacterial-derived necromass carbon, and straw increased both the bacterial- and fungal-derived necromass carbon contents. Straw had no influence on the ratios of microbial necromass carbon accounting for SOC and MAOC, but biochar decreased the ratios in the current study. Similarly, biochar mainly increased the fungal PLFA and total PLFA contents compared to CK, but straw increased bacterial PLFAs, fungal PLFAs and Actinomycetes PLFAs. Maize yield were increased by 7.44% and 9.16% by biochar and straw application, respectively. These results indicate that biochar stimulates fungal activities and turnover to contribute to the stable soil carbon pool and that biochar also improves POC contents to improve the soil organic carbon sink.